Biographical method and its applying in social sciences – an overview analysis - Gierczyk, Marcin; Dobosz, Dagmara (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
This article attempts to review publications from the Oxford library base, in which authors have used the method of biographical studies or mentioned its methodological aspects in the text. 30 works in the field of social sciences, published in 2010–2015 were subjected to the analysis. The identification of texts that met the inclusion criteria was made through analyzing the results of the search of preset keywords and their combinations in the database. The analysis showed a wide range of both subject areas, theoretical approaches as well as the mode of using the biographical method by researchers from various fields of science.